2017
DOI: 10.1186/s12877-017-0431-6
|View full text |Cite
|
Sign up to set email alerts
|

Managing multiple chronic conditions in the community: a Canadian qualitative study of the experiences of older adults, family caregivers and healthcare providers

Abstract: BackgroundThe prevalence of multiple chronic conditions (MCC) among older persons is increasing worldwide and is associated with poor health status and high rates of healthcare utilization and costs. Current health and social services are not addressing the complex needs of this group or their family caregivers. A better understanding of the experience of MCC from multiple perspectives is needed to improve the approach to care for this vulnerable group. However, the experience of MCC has not been explored with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
194
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(207 citation statements)
references
References 30 publications
10
194
0
3
Order By: Relevance
“…Such knowledge would enable pharmacy staff to offer more extensive carer support, such as signposting carers to external organisations. Other research has demonstrated that carers may not know which services are available to them [27][28][29] and that pharmacists can fulfil an important role as information providers and/ or care coordinators. [30] Participants emphasised that information on key support organisations such as Carers Australia was underutilised in practice and that they only became aware of these agencies following training in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Such knowledge would enable pharmacy staff to offer more extensive carer support, such as signposting carers to external organisations. Other research has demonstrated that carers may not know which services are available to them [27][28][29] and that pharmacists can fulfil an important role as information providers and/ or care coordinators. [30] Participants emphasised that information on key support organisations such as Carers Australia was underutilised in practice and that they only became aware of these agencies following training in this study.…”
Section: Discussionmentioning
confidence: 99%
“…International literature on intersectoral collaboration often describes intersectoral collaboration as challenging, especially when it concerns elderly people with multimorbidity (Curry & Ham, ; Goodwin, Dixon, Anderson, & Wodchis, ; Moeller, ; Ploeg et al, ; Shiner, Steel, & Howe, ). In this literature, such challenges are typically explained as related to fragmentation of health services due to medical specialization.…”
Section: Introductionmentioning
confidence: 99%
“…It is also evident that community pharmacy services need to meet the needs of the individual consumer, as well as the existing gaps in healthcare practice (Hossain et al, ). With respect to our study, there was some consensus that this individualised service was suitably placed within the pharmacy setting, with an acknowledgement that some carers may need more support than others, although they may be resistant to obtaining support for various reasons, such as pride or independence (Ploeg et al, ). An important component of equipping pharmacy staff to deliver a carer support service would be to include strategies that support staff to explore where carers are situated in their individual journey, and to be able to respond accordingly.…”
Section: Discussionmentioning
confidence: 97%